Treatment of POME by pilot plant anaerobic fluidised bed reactor - Mamun, Abdullah Al; Idris, A. (International Islamic University Malaysia, 2008)
A pilot scale anaerobic fluidised bed reactor (AnFBR) of 2000 L capacity was studied to determine its ability to treat palm oil mill effluent (POME). The pilot plant was operated at ambient temperature with diluted POME as substrate. It took 17 days for the start-up of the reactor with pre-seeded sand media. The mean influent concentration of BOD, COD and TSS were 1110, 2194 and 1004, respectively. The AnFBR was capable to remove a large portion of organics at relatively shorter retention time. Maximum and minimum COD removal efficiency of 85% and 65% were attained at a loading rate of 4.0 and 13.8 kgCOD/m3.d. BOD and TSS removal rates varied within the range of 64% - 91% and 68% - 89%, respectively. The average residual COD, BOD and TSS concentration was 330, 95 and 110 mg/L, respectively. The AnFBR exhibited less sludge production with lower values of sludge volume indices (SVI). Maximum and minimum effluent indices for the effluent were 35 mL/g and 11 mL/g, respectively. Low SVI values indicated that, anaerobic fluidised bed reactors generate less sludge with fast settling properties. Promising performance at ambient temperature and for detention time shorter than the present practices supported the possibility of AnFBR to pretreat POME to meet the new requirement set by the DOE Malaysia.